Viabilidade técnica para reuso de efluente oriundo de lavagem de veículos tratado por eletrólise e osmose inversa - Matter, Andréia (2022)
Car washing produces an effluent loaded with impurities that are impregnated in vehicles, together with detergents that change the characteristics of this effluent, constituting a significant source of COD. Due to the growing demand and scarcity of water all over the world, several solutions have been studied to promote the reuse of this effluent, avoiding the waste of drinking water and promoting cost reduction for companies. The physical-chemical treatment used in the treatment of these effluents does not reach the necessary parameters for reuse, but there are several efficient treatment technologies for this purpose. Thus, this study proposed the combination of the treatment process through electrolysis and reverse osmosis, in order to technically evaluate the feasibility of reusing the effluent generated in a vehicle wash. Electrolytic treatment uses electric current to remove pollutants, and membrane separation consists of removing substances using filtration membranes, this technique has great potential for application in reuse systems, as it produces a treated effluent with high levels of clarification. The effluent was characterized according to the physical-chemical parameters, then the electrolytic process was applied, evaluating the best treatment condition according to the THD applied, and then the previously treated effluent passed through the reverse osmosis membrane. Subsequently, pH, color, turbidity, phosphorus, total suspended solids, chemical oxygen demand and organic material were evaluated in order to compare the results of the treated effluent with the reuse parameters in accordance with current legislation. The combination of treatments showed values greater than 80% in the removal of chemical oxygen demand and organic material and efficiency in the removal of color, turbidity, total suspended solids and phosphorus above 99%. Making some adjustments in the process, these results make it possible to reach the requirements demanded by the legislation, allowing the reuse of the effluent in the process of washing vehicles.